RELATIONSHIP BETWEEN CARDIOVASCULAR RISK AND LUNG FUNCTION IN INDUSTRIAL WORKERS (CIPEEX, 2025)
Introduction: Obesity is considered a pandemic disease because it is highly prevalent in developed and developing countries and is associated with respiratory disorders. The waist-to-hip ratio (WHR) is not only an indicator of obesity but is also considered a cardiovascular risk factor. Objective: To relate cardiovascular risk to lung function in industrial workers. Methods: This was a cross-sectional analytical study involving workers in a construction materials industry. The sample consisted of 143 workers. The WHR was calculated by dividing the waist circumference by the hip circumference, and respiratory function was measured by spirometry. Workers were stratified according to WHR (low and high risk). Results: Forty-one (28.7%) of the industrial workers were at high risk, of whom 25 were female. Age was higher in workers with high cardiovascular risk. Peak expiratory flow (PFE) ((∆=0,55 L/s, p
Keywords: Waist-hip ratio; Cardiovascular risk; Lung function; Industrial workers